1998
DOI: 10.1046/j.1365-2141.1998.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype of adult and childhood acute promyelocytic leukaemia: correlation with morphology, type of PML gene breakpoint and clinical outcome. A cooperative Italian study on 196 cases

Abstract: Summary. Acute promyelocytic leukaemia (APL), characterized by a specific PML-RARa fusion gene resulting from translocation t(15;17) and by a high response rate to differentiation therapy with all-trans retinoic acid, presents clinical (varying WBC counts, age and treatment outcome), morphological (hypergranular M3 and hypogranular M3V) and molecular (three isoforms of PML breakpoint) heterogeneity.We correlated leukaemic immunophenotype with these aspects in 196 molecularly confirmed APLs (63 children and 133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
108
4
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(120 citation statements)
references
References 19 publications
7
108
4
1
Order By: Relevance
“…Factors associated with an inferior prognosis in t(15;17) APL include older age [3,5,7], increased WBC count at presentation [1,5,7,8], and the detection of the PML-RAR␣ translocation prod-in APL. Typical surface markers include CD13, CD33, and CD9 [12][13][14]. Atypical markers, including CD2 and CD34, have been reported [12,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with an inferior prognosis in t(15;17) APL include older age [3,5,7], increased WBC count at presentation [1,5,7,8], and the detection of the PML-RAR␣ translocation prod-in APL. Typical surface markers include CD13, CD33, and CD9 [12][13][14]. Atypical markers, including CD2 and CD34, have been reported [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Typical surface markers include CD13, CD33, and CD9 [12][13][14]. Atypical markers, including CD2 and CD34, have been reported [12,15]. Although the clinical relevance of these immunophenotypic markers is not clearly known, several groups have shown that expression of CD2 is associated with microgranular morphology (M3v) [16,17] and the bcr3 PML-RAR␣ isoform [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…Their study included 372 lymphoma patients and comprised a subgroup of 155 patients with diffuse large B-cell lymphoma (DLBCL) who underwent both 18 F-fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography (FDG-PET/CT) and unilateral bone marrow biopsy (BMB) of the iliac crest. Sensitivity of FDG-PET/CT and BMB were calculated using the combination of the two tests as reference standard.…”
mentioning
confidence: 99%
“…A joint study reported that morphologic variant subtype had, compared to the classic subtype, higher CIR and significant reduced OS [16]. CD34 expression in APL has been associated with hyperleucocytosis, bcr3 isoform, microgranular variant, and CD2 expression [17,18]. In our experience, isolated CD34 expression identified a subgroup with a classic morphology (79%), bcr1 prevalence (53%), higher rate of relapse (37% vs. 13.8% in the negative group, P 5 0.002), higher incidence of differentiation syndrome (55% vs. 12%, P 5 0.03) and lower OS (60% vs 95%, P 5 0.001).…”
mentioning
confidence: 99%